Effect of Subsurface Drip Irrigation on Potato Production - Neelam Patel; T.B.S. Rajput (Journal of Soil and Water Conservation, 2022)
Subsurface drip irrigation (SDI) is most advanced method of irrigation, applied the small amounts of water to the crop through the drippers placed below the soil surface. One of the most commonly discussed aspects of SDI system is installation depth of drip tape. Determining the appropriate depth of installation will always be challenging and requires consideration of soil structure, soil texture, crops root development pattern. Complexity inherent in this list has prevented tabulation of general recommendations for installation depths of SDI systems. The experiment was conducted on potato (var. Kufri Anand) during October to February for two years (2003-04 and 2004-05) in coarse textured soil. Drip tape was buried manually at depths of 0.0, 5.0, 10.0, 15.0 and 20.0 cm below the middle of ridge. Soil moisture distribution at different growth stages of potato and at different depths of placement of drip tape was monitored. When drip tape was placed at surface and buried at 5.0 cm soil depth, upward movement of water takes place, 21.5 per cent moisture was found at the surface at different growth stages of potato. When drip tape buried at the depth of 10.0, 15.0 and 20.0 cm, it was found that the water movement due to capillary forces is not sufficient and soil surface remains relatively dry. The maximum yield was recorded in treatment T3 during 2003-04 and 2004-05, which was followed by the treatment T2. Potato yield was significantly affected by the placement of drip tape and maximum yield can be obtained by applying the 23.6 cm of irrigation water and by placing the drip tape at 10.0 cm soil depth.